From the Foundation Up - Callahan, Daniel (The Hastings Center report, 2017)
In 2019, The Hastings Center will celebrate its fiftieth anniversary. It is more than a bit staggering to think how far we have come since 1969. When I floated the idea of a center on bioethics to my friend and neighbor, psychiatrist Willard Gaylin, at a Christmas party in 1968—even before the word “bioethics” was used—I had only the fuzziest idea of where that would take us. Neither Will nor I had run anything, nor did we know how to raise money to support an organization. We would and did learn how, but much of what we did in those early years was made up on the fly. We not only had to invent an organization but no less to invent a field of research and education on issues still little noticed by the public or academics. Out of curiosity, I recently googled “bioethics.” I was astonished at what I found and by the sheer quantity of what is going on.